Solar-powered refrigerator box - Tan, David Yuren. (2011)
This project has presented an opportunity to design a solar powered refrigerator. Literature reviews were conducted to investigate if such an idea was feasible. The various types of cooling technologies were reviewed and investigated. Vapor-compression cooling as well as phase change cooling is selected to be incorporated with existing photovoltaic technologies. The design intension of the solar refrigerator is to be robust and for outdoor usage where conventional electricity is not readily available.